Dental caries and oral health behavior assessments among portuguese adolescents. - Nélio Jorge Veiga; Maria Helena Ribeiro De Checchi; Johnny Martins; Inara Pereira da Cunha; Marcelo de Castro Meneghim; Maria José Correia; Patrícia Couto (Journal of Oral Research, 2020)
Introduction: Adolescents have a high risk of developing caries in Portugal. The present study is designed to assess dental caries experience among the adolescents by the application of DMFT index, characterize the oral health risk factors and to determine the association between caries experience and socio-demographic variables. The characterization of the oral health behaviors of adolescents of the central region of Portugal will help in the development of specific oral health education strategies to improve oral health among the local communities. Material and methods: A cross-sectional study was conducted among a convenient sample of 694 adolescents aged 12 to 18 years attending public schools in two Portuguese districts using a structured questionnaire designed to investigate oral health and behavior of participants. In addition, a clinical examination was carried out noting the decayed, missing and filled teeth. A descriptive analysis of the variables was performed using the Chi-square, Mann-Whitney and Kruskal-Wallis tests (p<0.05). A multivariate analysis was applied for analysis of the association between variables. Results: The mean DMFT index score of 2.91±2.9 was obtained. Of the total sample, 73% consumed sugary food daily, 50.1% considered having good oral health and 70.8% did not report pain in the last 12 months. Most adolescents (79.4%) brushed their teeth daily and 60% did not use dental floss. Of the total sample, 96.4% had a dental appointment in the last 12 months, 46.4% of which was for preventive purposes. Applying the Chi-square statistical test, we verified that the adolescents who brush their teeth daily presented a good perception about their oral health (p<0.001), the DMFT index scores were associated with the residence area (p=0.01) and the presence of dental caries was associated with the perception of oral health (p=0.049) and sugary food intake (p=0.029).Conclusion: Portuguese adolescents presented a low DMFT index. The DMFT index was associated with residence area, perception of oral health and sugary food intake. Daily toothbrushing was associated with self-perception of oral health. It is suggested that oral health promotion and prevention programs should aim to reduce the risks of oral disease development.